2008
DOI: 10.1227/01.neu.0000320422.54985.6d
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of Cholinergic Rat Basal Forebrain Neurons After Experimental Subarachnoid Hemorrhage

Abstract: The present study provides evidence for a decrease of cholinergic BFB neurons after SAH. The direct effect of blood in the basal cisterns seemed to result in an enduring tissue hypoxia as a significant mechanism for cholinergic degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The findings of early neuronal damage were independent of peak ICP and the amount of subarachnoid blood. Using the ICP-controlled shunt model, the results extend prior findings [ 13 - 18 ] and suggest that CPP depletion at the time of SAH potentially triggers processes that eventually result in EBI after SAH.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The findings of early neuronal damage were independent of peak ICP and the amount of subarachnoid blood. Using the ICP-controlled shunt model, the results extend prior findings [ 13 - 18 ] and suggest that CPP depletion at the time of SAH potentially triggers processes that eventually result in EBI after SAH.…”
Section: Discussionsupporting
confidence: 83%
“…It has been demonstrated that subarachnoid blood can cause direct brain damage, late rCBF reduction, and neuronal and astrocytic apoptosis independent of initial ICP increase [ 14 - 18 ]. However, we could not establish any relationship between the amount of subarachnoid blood and the degree of early (24 h) neuronal cell damage, either in close proximity to the brain surface (basal cortex) or in deep brain regions (hippocampus).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that there is no direct vascular damage in this model, the distribution of blood is similar to that often seen after clinical SAH (Prunell et al, 2002), which most commonly involves the anterior circulation. Loss of forebrain cholinergic neurons and markers of inflammation and cell death are found in at least some animals up to a week after the experimental hemorrhage (Prunell et al, 2005a, b; Lohr et al, 2008). Further, a subset of animals show neurological deficits (Prunell et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Conditions predominantly associated with a loss of one specific cell population, such as amyotrophic lateral sclerosis, Parkinson’s disease, or subarachnoid hemorrhage, may be targeted using specifically pre-differentiated cell grafts. In the case of traumatic or ischemic brain injury, a whole tissue segment (including neurons, glia, and vascular cells) has to be replaced by cells, which are able to differentiate into all lost cell types; alternatively, a heterogeneous graft containing different cell populations can also be used (Schouten et al, 2004; Molcanyi et al, 2007; Riess et al, 2007; Lohr et al, 2008; Burns et al, 2009; Richardson et al, 2010; Benchoua and Onteniente, 2011). …”
Section: Introductionmentioning
confidence: 99%